(دراسة فكرة ثعلب عن قاعدة النحوي (ممثِّلُ أهل النحو من المذهب الكوفي: Study of the Idea of Tsa'lab on the Rule of Grammar (Representative of Grammarians from the Kufi School) - Sirfi Fatoni, Ahmad (Institut Kariman Wirayudha Sumenep, 2025)
Abstract This research reveals Tsa'lab, a world-famous Kufi grammarian, his idea and the most important representative of the Kufi school. Such research is still rare in Indonesia, and this research is essential and prestigious in revealing a person who has a great contribution to building the grammar base. The type of this research is qualitative research using descriptive and critical analysis. The discoveries are as follows: (1) Tsa'lab believed that the alif in the dual noun is a substitute for the two dhammahs in Zayd and Zayd, and that the waw is a substitute for the three dhammahs in Zayd, Zayd and Zayd, and this is a unique idea of ​​Tsa’lab as a representative of the Kufi school; (2) Tsa'lab added the verbs نشب and قام to the sisters of كادَ; (3) Al-Kisa'i and Al-Farra' believed that the function of inna can be invalidated if inna’s ism is far from it, and we see that Tsa'lab sing the words of Badui people:فليت ابن جوَّابٍ من الناس حظُّنا * وأنَّ لنا في النار بعدُ خلودُ.” He says after it: